Combining ability for selected characters in winter rye. - Kolasińska, Irena; Węgrzyn, Stanisław (Plant Breeding and Seed Science, 2003)
General (GCA) and specific (SCA) combining abilities for four agronomic characters were determined in two experiments. The first included 24 F1 hybrids produced by crossing 6 restorers (R) to four CMS single crosses (CMS-SC). The second experiment included 20 F1 hybrids derived by crossing ten restorers to two CMS single crosses. The following characters were assessed: grain yield, heading date, plant height and lodging. Analysis of the combining ability was carried out according to the factorial mating design (North Carolina II Design) with the WAKOMBK (TP) computer software. General combining ability of both males and females was significant for all the characters in the experiment 1. In the second experiment GCA of females proved to be significant for all the characters, but GCA of males was significant only for plant height. Significant specific combining ability was detected only for the heading date in the first experiment and for all the characters except for plant height in the second one. Additive gene effects seems to be more important than nonadditive gene effects in controlling all the characters under study. The restorers and CMS single crosses with significant and favourable GCA effects were selected for further stages of hybrid breeding programme.